Lectins and their application to clinical microbiology. - Slifkin, M (1990)
Lectins are generally associated with plant or animal components, selectively bind carbohydrates, and interact with procaryotic and eucaryotic cells. Lectins have various specificities that are associated with their ability to interact with acetylaminocarbohydrates, aminocarbohydrates, sialic acids, hexoses, pentoses, and as other carbohydrates. Microbial surfaces generally contain many of the sugar residues that react with lectins. Lectins are presently used in the clinical laboratory to type blood cells and are used in a wide spectrum of applications, including, in part, as carriers of chemotherapeutic agents, as mitogens, for fractionation of animal cells, and for investigations of cellular surfaces. Numerous studies have shown that lectins can be used to identify rapidly certain microorganisms isolated from a clinical specimen or directly in a clinical specimen. Lectins have been demonstrated to be important diagnostic reagents in the major realms of clinical microbiology. Thus, they have been applied in bacteriology, mycology, mycobacteriology, and virology for the identification and/or differentiation of various microorganisms. Lectins have been used successfully as epidemiologic as well as taxonomic markers of specific microorganisms. Lectins provide the clinical microbiologist with cost-effective and potential diagnostic reagents. This review describes the applications of lectins in clinical microbiology.